2007
DOI: 10.1021/nl070814e
|View full text |Cite
|
Sign up to set email alerts
|

Voltage Generation from Individual BaTiO3 Nanowires under Periodic Tensile Mechanical Load

Abstract: Direct tensile mechanical loading of an individual single-crystal BaTiO(3) nanowire was realized to reveal the direct piezoelectric effect in the nanowire. Periodic voltage generation from the nanowire was produced by a periodically varying tensile mechanical strain applied with a precision mechanical testing stage. The measured voltage generation from the nanowire was found to be directly proportional to the applied strain rate and was successfully modeled through the consideration of an equivalent circuit fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
112
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(112 citation statements)
references
References 19 publications
0
112
0
Order By: Relevance
“…Following this initial discovery, both direct current [23,499,500] and alternating current [24] ZnO nanogenerators have been developed. In addition, nanogenerators based on other materials, such as GaN nanowires [501][502][503], InN nanowires [504], AlGaN nanocones [505], CdS nanowires [506], ZnO/ZnS heterojunction nanowires [507], lead zircornia titanates (PZT) nanofibers [508], nanoribbons [509][510][511][512][513], nanotubes [514], and single crystalline nanowires [515], BaTiO 3 nanowires [516], NaNbO 3 nanowires [517], and poly(vinylidene fluoride) (PVDF) nanofibers [518,519], have shown promising potential for enhancing nanogenerator performance. Consequently, a worldwide effort has been launched in this regard, forming a new research field in nanotechnology and energy science [520].…”
Section: Piezoelectric Nanogeneratorsmentioning
confidence: 99%
“…Following this initial discovery, both direct current [23,499,500] and alternating current [24] ZnO nanogenerators have been developed. In addition, nanogenerators based on other materials, such as GaN nanowires [501][502][503], InN nanowires [504], AlGaN nanocones [505], CdS nanowires [506], ZnO/ZnS heterojunction nanowires [507], lead zircornia titanates (PZT) nanofibers [508], nanoribbons [509][510][511][512][513], nanotubes [514], and single crystalline nanowires [515], BaTiO 3 nanowires [516], NaNbO 3 nanowires [517], and poly(vinylidene fluoride) (PVDF) nanofibers [518,519], have shown promising potential for enhancing nanogenerator performance. Consequently, a worldwide effort has been launched in this regard, forming a new research field in nanotechnology and energy science [520].…”
Section: Piezoelectric Nanogeneratorsmentioning
confidence: 99%
“…10,14,27,29 Theories and experiments on FNCs taking various forms such as nanodisks ͑ND͒, nanorods ͑NR͒, nanowires ͑NW͒, and nanotubes ͑NT͒ have indicated that their phase-transition or near-phase-transition properties are very sensitive to the applied stress. [33][34][35][36][37][38][39][40][41][42] In these investigations, stresses produced by surface tension and external mechanical loads have been found to significantly affect the Curie temperature, polarization, susceptibility and other related properties near the ferro/ paraelectric phase transition, resulting in remnant polarization and coercive fields that may exceed the bulk values. Indeed, under an uniaxial load of suitable magnitude and frequency, an appropriately dimensioned ferroelectric NW may produce a sizeable ac voltage, sufficient as a nanopower source for energy harvesting, or as an effective nanomechanical sensor.…”
Section: ͑Pzt͒mentioning
confidence: 99%
“…Indeed, under an uniaxial load of suitable magnitude and frequency, an appropriately dimensioned ferroelectric NW may produce a sizeable ac voltage, sufficient as a nanopower source for energy harvesting, or as an effective nanomechanical sensor. 41,42 It is clear that FPV effects may become very small when the average internal electric field in FNC is zero. [16][17][18][19][20][21][22][23][24] In this case, the photocurrent is only due to charge transport via diffusion.…”
Section: ͑Pzt͒mentioning
confidence: 99%
“…To observe piezoelectricity, the conventional method is to measure the dipole induced by strain, as carried out in nanowires 21 and very recently in supported MoS 2 on polymer substrates 22 . However, the interaction between the two-dimensional crystal and the substrate in such flexible devices makes quantitative determination of the intrinsic piezoelectric properties challenging.…”
mentioning
confidence: 99%